Key Factors That Trigger People to Support Street Children in Indonesia - Somariah Fıtrıanı (Sakarya University Journal of Education)
This study has an attempt to elaborate some factors affecting the establishment of “free schools” by community participant, which are intended to serve for street children and poor children (marginal children) in urban areas who do not have access to get proper education on account of economic and social issues. Qualitative approach was employed by using Miles and Hubberman model analysis to analyze the data. The data were taken from three schools (Sekolah Darurat Kartini, Sekolah Master and Sekolah Himmata), which are situated in Jakarta and Depok City. Participant observation, face-to-face interviews, documentary research studies, Internet online articles and literature reviews were used in data collection process. Some key respondents to obtain the data are the founders of schools, social guardians, pupils, parents and alumni. As a key instrument, the researcher also took part in the Sekolah Darurat Kartini’s activities for around two years from the end of 2011 until the middle of 2013. The research findings have revealed that the key factors of such schools’ establishment are altruism, determination and self-actualization are grouped into internal factors while parent’s upbringing, economic, social and educational background, wide communication network are grouped into external factors. Even though these factors are interrelated and interwoven holistically. Altruism is the most triggering primary factor what make the founders of the schools act and behave differently for the sake of other people’s future, particularly to street children. As future generations, street children have right to obtain access for education equally. To sum up, the provision and establishment of such schools bring a greatest impact to students’ development and at the end it benefits the nation.